Tenacibaculum maritimum can boost inflammation in Dicentrarchus labrax upon peritoneal injection but cannot trigger tenacibaculosis disease - Ferreira, Inês A.; Santos, Paulo; Moxó, Javier Sanz; Teixeira, Carla; do Vale, Ana; Costas, Benjamin (Frontiers in Immunology, 2024)
Despite being a bacterial pathogen with devastating consequences, Tenacibaculum maritimum’s pathogenesis is not fully understood. The aim of the present study was to elucidate if different inoculation routes (intraperitoneal - i.p - injection and bath challenge - known to induce mortality) can induce tenacibaculosis (i.e., using the same T. maritimum inoculum), as well as evaluate the short-term immune response of European sea bass (D. labrax). Additionally, the host response against i.p. injection of extracellular products (ECPs) was also studied. Fish were i.p. challenged with 5.5 × 105 CFU mL-1 of T. maritimum cells with or without ECPs (BECPs and BWO, respectively), ECPs alone or marine broth (mock). Another group of fish was bath-challenged with 5.5 × 105 CFU mL-1 to confirm the virulence of the bacterial inoculum. Undisturbed specimens were used as controls. The severity of both challenges was determined by following percentage survival . Blood, liver and head-kidney samples were collected at 0, 3, 6, 24 and 48 h post-challenge for assessing immune parameters, oxidative stress and gene expression. Total and differential peritoneal cell counts were performed. The presence of viable bacteria in the blood and peritoneal cavity was studied. Symptoms of tenacibaculosis, such as skin/fin abrasions, were only observed in the bath-challenged fish, where 0% survival was recorded, whereas 100% survival was observed after i.p. injection of the same bacterial inoculum . An increase in total leukocyte numbers in the peritoneal cavity was observed 3 h post-injection of BECPs when compared to the other treatments. Blood total leukocytes, lymphocytes, and thrombocyte numbers dropped after the challenge, mainly in fish challenged with BECPs. At 48 h post-challenge, bactericidal activity in the plasma increased in fish injected with bacteria (with and without ECPs). The same tendency was seen for some of the oxidative stress parameters. The increased expression of il1β, il6, il8, and hamp1 in fish challenged with ECPs and BECPs suggests a more exacerbated pro-inflammatory response in the head-kidney against these inocula. The infection trial and the observed immune responses showed that the infection route is a determinant factor regarding T. maritimum-induced pathogenesis in European sea bass.